Crescendo : Steinway’s growth strategy - Calkins, Tim (SAGE business cases., 2023)
As executives at the Steinway prepared the piano company to go public in 2022, the firm Damen Investments eyed the intriguing brand as having great potential. A new equity analyst at Damen, Vicki Xu, was tasked with determining if the Steinway brand and the company’s growth prospects hit all the right notes. If it had significant growth potential, the investment likely would make sense. If not, then the investment would not work well. Damen invested only in firms with strong growth potential over a long horizon-a decade or more. The storied brand, founded in 1853 in New York City, had long since developed a reputation for crafting the ultimate in quality and gained a loyal following among top pianists and musicians. With sales in 88 countries, Steinway was a global brand and business. Asia was a vital region for growth, especially China, where sales reached $117 million in 2021. That same year, overall revenue for Steinway was $538.4 million, up by a compound annual growth rate of 6.9 percent from 2016, when sales reached $386 million. In the company’s IPO filings, Steinway executives presented an optimistic outlook. According to the Steinway team, the company was a promising player in the global luxury industry. Steinway expected to benefit from market trends, and the number of high-net-worth individuals was growing worldwide-particularly in China. Additionally, the company was expanding sales of its Spirio line, focusing on wealthy buyers who could not play the piano.